The role of airborne transmission in a large single source outbreak of SARS-CoV-2 in a Belgian nursing home in 2020 - Bea Vuylsteke; Lize Cuypers; Guy Baele; Marianne Stranger; Sarah Lima Paralovo; Emmanuel André; Joke Dirks; Piet Maes; Marie Laga (Epidemics, 2022)
Objectives: To better understand the conditions which have led to one of the largest COVID-19 outbreaks in Belgian nursing homes in 2020. Setting: A nursing home in Flanders, Belgium, which experienced a massive outbreak of COVID-19 after a cultural event. An external volunteer who dressed as a legendary figure visited consecutively the 4 living units on December, 4th and tested positive for SARS-CoV-2 the next day. Within days, residents started to display symptoms and the outbreak spread rapidly within the nursing home. Methods: We interviewed key informants and collected standardized data from all residents retrospectively. A batch of 115 positive samples with a Ct value of < 37 by qRT-PCR were analyzed using whole-genome sequencing. Six months after the outbreak, ventilation assessment of gathering rooms in the nursing home was done using a tracer gas test with calibrated CO2 sensors. Results: Timeline of diagnoses and symptom onsets clearly pointed to the cultural event as the start of the outbreak, with the volunteer as index case. The genotyping of positive samples depicted the presence of one large cluster, suggesting a single source outbreak.By the end of December, a total of 127 residents and 40 staff were diagnosed with SARS-CoV-2 since the beginning of the outbreak. The attack rate among residents was 77 % and significantly associated with presence at the event but not with close contact or mask wearing. The ventilation assessment showed a high background average CO2 level in four main rooms varying from 657 ppm to 846 ppm. Conclusions: Our investigation shows a rapid and widespread single source outbreak of SARS-CoV-2 in a nursing home, in which airborne transmission was the most plausible explanation for the massive intra-facility spread. Our results underscore the importance of ventilation and air quality for the prevention of future outbreaks in closed facilities.